Genomic analysis of the Staphylococcus pseudintermedius mobilome associated with antimicrobial resistance - Morais, Catarina; Costa, Sofia Santos; Hanke, Dennis; Santos, Ana; Krüger-Haker, Henrike; Pomba, Constança; Feßler, Andrea T.; Schwarz, Stefan; Couto, Isabel (Frontiers in Microbiology, 2025)
The increasing antimicrobial resistance (AMR) in Staphylococcus pseudintermedius causing skin and soft-tissue infections (SSTIs) in companion animals is a public health concern. The aim of this study was to verify if mobile genetic elements (MGEs), in particular plasmids, are related to the carriage of AMR genes among circulating and clinically relevant S. pseudintermedius. In total, 56 S. pseudintermedius, representing predominant and emerging clonal lineages associated with SSTIs in dogs and cats collected in Lisbon (Portugal), were subjected to plasmid DNA extraction and digestion with EcoRI and XbaI. Each unique restriction pattern was assigned to a plasmid profile. A subset of 17 strains was further selected for hybrid whole genome sequencing (WGS) on Oxford Nanopore MinION and Illumina MiSeq platforms. Thirty-one of the 56 S. pseudintermedius strains carried one or more plasmid(s), mostly of small or medium sizes, corresponding to eight plasmid profiles. Two of the identified plasmids carried AMR determinants; plasmid pSP-G3C4, isolated from ST71 strains, carried the tetracycline resistance gene tet(K) and plasmid pSP5912, isolated from a ST2061 strain, harbored the qacG biocide resistance gene. Other AMR determinants were detected as part of MGEs integrated into the bacterial chromosomal DNA, namely Tn552, Tn552-like, Tn553, Tn916, Tn5405-like, Tn5801, Tn5801-like GI6287 and pRE25-like elements. In addition, a new chromosomal cassette, carrying fusC, was identified in a ST1183 strain. The 12 methicillin-resistant S. pseudintermedius studied carried staphylococcal cassette chromosome mec (SCCmec) type III (n = 5), SCCmec type IVg (n = 3), SCCmecNA45 (n = 1), ΨSCCmec57395 (n = 1), the recently described cassettes SCCmec7017–61515 (n = 1), or SCCmec type V(T)SL/154 (n = 1). Most strains carried intact prophages without AMR determinants. Intact restriction-modification systems were detected in 12 out of the 17 strains and CRISPR/Cas in five strains, four of which were methicillin-susceptible. The results of this study suggest that the AMR content in S. pseudintermedius is mainly related to MGEs integrated into the chromosomal DNA rather than located on plasmids. These results provide important insights that may lead to a better understanding of multidrug resistance in S. pseudintermedius towards improved SSTIs treatment in companion animals.